Monitoring the impact of COVID-19 in Myanmar: Mechanization service providers - May 2020 survey round - Takeshima, Hiroyuki; Win, Myat Thida; Masias, Ian (International Food Policy Research Institute, 2020)
Agricultural mechanization service providers (MSP) are crucial to enabling smallholder farmers to undertake a range of power-intensive farm and post-harvest operations in a timely manner. These operations are important for food production and farm income. MSPs are capital-intensive operations. The economic viability of these businesses is highly sensitive to capacity utilization, which generates the cash flow needed to repay equipment loans; to prices of imported capital goods, including machines, equipment, and fuels; and to the availability of machine operators, among others. Hence, the operations of MSPs are sensitive to restrictions on mobility and trade. The COVID-19 pandemic in Myanmar, the restrictions imposed as policy responses to control the spread of the virus, and the associated market disruptions affect the operations of MSPs across the country. However, the specific impacts MSPs experience depends on factors specific to different regions and states. Measures to support MSPs and to ensure farmer access to their services should be guided by an understanding of the situation on the ground.